STRATEGI PEMBUATAN KONTEN DI INSTAGRAM DALAM UPAYA BRANDING UNIVERSITAS BINA DARMA - Natasha Rahma Utami; Isnawijayani, Isnawijayani (Bajang Institute, 2025)
This research aims to analyze content creation strategies on Instagram in an effort to enhance the branding of Bina Darma University. The background of this study is the importance of social media, particularly Instagram, as an effective medium for disseminating information and building a positive image of higher education institutions. The method used is a qualitative approach with a case study method, focusing on the official account @pmb_univ.binadarma as a promotional medium. Data were collected through in-depth interviews, direct observation, and documentation, involving marketing managers, marketing staff, and internship students. The results of the study show that Instagram plays a strategic role in attracting the attention of prospective students through the presentation of informative, creative, and visually appealing content. The application of the AAKR model (Awareness, Attention, Knowledge, Response) and the principles of creative communication helps improve audience interaction and build closeness with the target audience. Consistency in posting schedules and the use of interactive features such as polls, Q&A, and reels also contribute to increased engagement. This research is expected to serve as a strategic reference for other higher education institutions in optimizing social media as an effective branding tool